Software Risk Management Approaches in Large-Scale Systems: A Critical Examination (International Journal of Innovative Research in Computer Science & Technology, 2022)
For a long time, software industry  researchers have worked on risk supervision solutions.  Software risk supervision is a computer engineering  technique that includes identifying risks, estimating risks,  mitigating risks, and monitoring them. It provides a  structured framework in which to make informed decisions  about software development issues. Because of its  complexity, measuring risks in a large-scale system is more  challenging. Large-scale systems are difficult to build since  numerous hazards may emerge throughout the process. Risk  factors in large-scale systems vary from those in small  systems, particularly in terms of independent components.  This article explains the distinction among high-level and  low-level system, as well as a comprehensive list of risk  variables. The tools from the literature are further classified  into subcategories based on their suitability. We provide a  thorough comparison study of several software associated risk supervision replicas with certain frequently recognized  characteristics, and then classify them depending on the  strictness of the respective hazards.
Keywords: Risk supervision; High-level System; Risk Issues; Risk Supervision Tool